DDoS attack detection method based on conditional entropy and GHSOM in SDN - Junfeng TIAN; Liuling QI (Tongxin xuebao)
Software defined networking (SDN) simplifies the network architecture,while the controller is also faced with a security threat of “single point of failure”.Attackers can send a large number of forged data flows that do not exist in the flow tables of the switches,affecting the normal performance of the network.In order to detect the existence of this kind of attack,the DDoS attack detection method based on conditional entropy and GHSOM in SDN (MBCE＆amp;G) was presented.Firstly,according to the phased features of DDoS,the damaged switch in the network was located to find the suspect attack flows.Then,according to the diversity characteristics of the suspected attack flow,the quaternion feature vector was extracted in the form of conditional entropy,as the input features of the neural network for more accurate analysis.Finally,the experimental environment was built to complete the verification.The experimental results show that MBCE＆amp;G detection method can effectively detect DDoS attacks in SDN network.